Hubungan Rasio Lebar Bahu dan Panjang Leher terhadap Daya Tahan Kardiorespiratori pada Anggota Tim Bantuan Medis Baswara Prada - Agus Pramana Shakti Manik Artha; Tanjung Subrata; Fransiscus Fiano Anthony Kerans (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2024)
[The Relationship between Shoulder Width and Neck Length Ratio on Cardiorespiratory Endurance in TBM Baswara Prada Members] Cardiorespiratory endurace is the ability of the heart-lung system and muscles used to deliver oxygen during sustained physical activity. Cardiorespiratory endurance for each body type (somatotype) is generally different. Somatotype differences in this study included the ratio of shoulder width to neck length. This study aims to determine the relationship between the ratio of shoulder width and neck length to the cardiorespiratory endurance of TBM Baswara Prada members. The method of this study was observasional with analytical cross sectional. In this study, sampling was carried out using the non-probability sampling method with consecutive sampling techniques. This study was conducted on 70 student who are member of TBM Baswara Prada. This study used primary data through observation or direct observation of research subjects according to the inclusion and exclusion criteria. Data were analyzed using the Pearson correlation statistical test with normally distributed data. The results were as follows: The average ratio biacromial width and neck length and cardiorespiratory endurance; 2.83+0.35; 59.25+11.91 respectively; and the relationship of both was strong negative significance (0.05) with a correlation coefficient (-0.720). The conclusion of this study is that there is a relationship between the ratio of biacromial width and neck length with cardiorespiratory endurance which is negative and significant The present study is anticipated to enhance the caliber of TBM Baswara's human resources in selecting members with good cardiorespiratory endurance indicators by using the ratio of shoulder width to neck length.